Psychological Well-Being pada Dosen Swasta di Kota Padang yang Belum Tersertifikasi: Analisis Peranan Character Strengths dan Social Support - Rina Mariana; Isna Asyri Syahrina (Universitas Muhammadiyah Metro, 2025)
This study examines the role of character strengths and social support in predicting psychological well-being among non-certified private university lecturers in Padang City, Indonesia. A quantitative correlational design was employed using purposive sampling with 114 lecturers who met predefined inclusion criteria. Data were collected through standardized psychological scales assessing character strengths, social support, and psychological well-being. Statistical analyses, including normality, linearity, multiple regression, and coefficient of determination tests, were performed using SPSS. The findings reveal that both character strengths and social support significantly predict psychological well-being (p < 0.001). RÂ² = 0.813, this result indicates that these predictors jointly explain 81,3% of the variance in psychological well-being. These results underscore the importance of promoting positive character development and enhancing social support systems to improve lecturers’ psychological well-being. Future research should explore contextual and organizational factors that may influence psychological well-being within higher education settings.